DEVELOPMENT OF ENTREPRENEURIAL COMPETENCIES IN THE ECONOMY (EVIDENCE FROM DIGITAL ENTREPRENEURSHIP) - Nikolaevich Dudin, Mihail; Fedorovich Shakhov, Oleg; Pavlovna Ivashchenko, Natalia; Sergeevna Shakhova, Margarita (Revista Inclusiones, 2021)
The article defines the essence of competencies and in particular, entrepreneurial competencies, reveals the development features of the entrepreneurial competencies in the context of the digital economy, as well as considers the formation mechanisms of digital competencies, and offers the ways of their further development. The purpose of the article is to consider ways, methods, and tools for the development of entrepreneurial competencies in regard to digital entrepreneurship. The methodology includes a set of empirical (observation, generalization, inference) and quantitative (statistical analysis, dynamic analysis) research methods. Main research results. In terms of professional digital skills, the main objectives in the education segment include implementing approach taking into account the competence, end-to-end (cross-platform) digital competence; increasing the proportion and improving the training quality of ICT specialists; implementing a career guidance program in schools, vocational schools, and universities to identify the ablest students to work in the digital sphere; developing social elevator in the ICT sector, encouraging the development of youth digital entrepreneurship; updating the Standard Classification of Occupations, i.e., developing and approving the digital professions list (based on the requirements of the labor market and digital trends), and implementing them in specialized educational institutions. Applicable scope. The need to reform the education system in accordance with modern requirements, revision of curricula in accordance with the needs of the labor market and the requirements of employers. Conclusion. Today, digitalization and cross-platform competence are the main trends in the general labor market. The ability to use digital technologies in work is gradually becoming necessary for most specializations and occupations, i.e. is becoming end-to-end or cross-platform. Through the use of online technologies, citizens can more effectively acquire knowledge, abilities, and skills in many other areas (for example, learn languages, subjects, learn professions, etc.). Accordingly, digital literacy should be one of the key entrepreneurial competencies.